A review of thermochemical biomass conversion combined with Stirling engines for the small-scale cogeneration of heat and power - Schneider, Tanja; Müller, Dominik; Karl, Jürgen (Renewable & Sustainable Energy Reviews, 2020)
Small-scale cogeneration of heat and power using solid biomass fuels is a promising option for the decentralization of the energy supply in the future. In this context, numerous research activities and commercial developments focus on combined systems with Stirling engines and thermochemical conversion of biomass. However, only few of the reviewed concepts and developments achieved to provide commercially successful products. The main problems are ash melting issues and fouling on heat exchanger surfaces as a consequence of the required high temperature levels at the hot side of the Stirling engine. The systems reveal short operation and maintenance intervals as well as mechanical issues due to still insufficiently technically mature Stirling engine technologies. Recent research therefore focuses on the combination of Stirling engines with fluidized bed combustion as homogeneous temperature distribution, enhanced heat transfer and fuel flexibility provide theoretically advantages. Nevertheless, due to the thermodynamic boundary conditions and constraints the electrical efficiency of biomass-fired Stirling engines is limited to 15–20%. However, with the additional utilization of thermal energy at an overall fuel utilization efficiency above 80%, such a system can provide an attractive small-scale CHP solution.
CRIS-Team Scopus Importer:2020-09-18
Keywords: Biomass; Combined heat and power; Small-scale CHP; Stirling engine; Thermochemical conversion